Mediating Effects of Process Improvement between Lean Manufacturing and Financial Performance - Abdurezzag .M. Ataalah; Aref. M. Alkelani; Abduallah .M. shwairef (Surman Journal of Science and Technology, 2023)
Abstract: In today's competitive business environment, companies aim to boost financial performance (FP) through effective strategies. Lean Manufacturing (LM) optimizes resources while delivering customer value. Although LM's impact on FP is recognized, the mediating role of Process Improvement (PI) remains an area of interest. This study investigates the relationships among LM, PI, and FP within Libyan manufacturing companies. The primary objective is to explore the dynamics among Lean Manufacturing (LM), Process Improvement (PI), and Financial Performance (FP) within the context of Libyan manufacturing. By enhancing comprehension of these interrelationships, this research aims to provide insights for manufacturing entities. An empirical survey was conducted across various Libyan manufacturing firms to achieve this goal. The survey included dimensions related to LM, PI, and FP. Collected data underwent multivariate techniques, structural equation modeling, and measurement model validation for comprehensive analysis. Results confirm a positive correlation between LM and PI, signifying the effectiveness of incorporating lean practices for process efficiency. However, a notable finding suggests a lack of significant impact of PI on FP, challenging the notion that process improvement directly leads to better financial outcomes. Additionally, the hypothesized mediating role of PI in the LM-FP connection lacks empirical support, implying a more complex relationship. In conclusion, this study highlights the complex interplay of LM, PI, and FP in Libyan manufacturing, emphasizing nuanced strategies for financial optimization. Further research is needed to validate and expand these context-specific insights, offering empirical guidance to organizations navigating lean practices and financial performance. . Keywords: Lean Manufacturing- Process Improvement- Financial Performance- Libyan Manufacturing Companies